Hand hygiene and water quality assessment in schools of Muthanna province, Southern Iraq - Saad M Hantoosh (Journal of Infection in Developing Countries)
Introduction: The severe drought and prolonged heat waves in Iraq have adversely affected the water quality supplied to public facilities. Schools are among the most affected facilities by water scarcity. This work aims to evaluate the level of students’ hand hygiene, and the quality of municipal (MW) and drinking water (DW) in some schools of Al-Muthanna Province, Iraq.